Assessment of heavy metals concentration of Mapanuepe Lake, Zambales, Philippines - Ma. Shiela G. Mendoza; Danilo V. Rogayan Jr. (Institute of Advanced Engineering and Science, 2024)
Despite the absence of recent research, Mapanuepe Lake in the Philippines has been a significant environmental concern due to potential heavy metal contamination. Hence, the study assessed the heavy metal concentration of water and surface sediments and identified the other physicochemical properties of Mapanuepe Lake in San Marcelino, Zambales, Philippines. This descriptive research employed physical profiling and physicochemical characterization of water and surface sediments of the lake. Six sampling stations in the lake were selected based on their current land use and nearness to the point source of heavy metal pollution. The study found that the Mapanuepe Lake is a thriving place for algae and zooplankton. The heavy metal concentration of the lake water and sediment sample is within the standard limit. The water conductivity is considered to be within the standards. In terms of pH level, the sampling sites obtained a pH level within the acceptable limit. The concentration of heavy metals in the lake water and sediments is generally within the standard limit. Other physicochemical properties are also in the acceptable range. The community people and local government must collaborate to implement the crafted strategic environmental sustainability plan, which includes biodiversity conservation and ecotourism promotion. Likewise, the study provides updated and comprehensive data on the status of the lake's heavy metal concentration for policy formulation and further research.